Sensitivity to marketing and the importance of emotional intelligence in small and medium-sized service firms - Suárez-Vázquez, Ana; Iglesias-Argüelles, Victor; Trespalacios-Gutiérrez, Juan (Wydawnictwo Uniwersytetu Ekonomicznego we Wrocławiu, 2014)
This paper examines how the perceived sensitivity of customers to marketing policies affects the importance placed on emotion management. The results of the structural equations modelling of data collected from managers of 128 small and medium-sized service firms suggest that the importance placed on the perception of emotion grows in accordance with an increase in the perceived market sensitivity to advertising. The hypotheses concerning the influence of consumer price sensitivity on the importance of dealing with emotions in service firms were not confirmed
Argumenta Oeconomica, 2014, Nr 1 (32), s. 75-93
Keywords: emotional intelligence; service marketing; small and medium enterprises